Analysis of Translation Techniques in Indonesian Subtitles of Interstellar Movie - Muhammad Raka Iqbal Fadil Muharom; Otong Setiawan Djuharie (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the translation techniques in Indonesian subtitles of Interstellar (2014), applying Vinay and Darbelnet's framework. Through a qualitative descriptive analysis of 1,903 English-Indonesian subtitle pairs from Google TV, the research identifies the distribution patterns of seven translation procedures: borrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. Results indicate literal translation dominates with 636 instances (33.42%), followed by modulation (489 cases, 25.70%) and transposition (362 cases, 19.02%). Borrowing accounts for 247 cases (12.98%), while equivalence, adaptation, and calque represent 3.57%, 2.84%, and 2.47%, respectively. The nearly balanced use of direct techniques (48.87%) and oblique techniques (51.13%) demonstrates strategic approaches in professional translation. The predominance of literal translation suggests structural compatibility between English and Indonesian, while significant modulation and transposition usage reveal necessary adaptations for cultural and linguistic differences. Technical terminology often favors borrowing, and cultural references require adaptation. This research provides empirical evidence for professional audiovisual translation practices.